Spontaneous pneumothorax: intubated or non-intubated surgery? - V.V. Tkalich; Yu.V. Nedilia; V.I. Borysova; O.V. Galiiev; S.I. Savoliuk (Medičnì Perspektivi)
The aim of our clinical study was to justify and implement non-intubated video assisted thoracic surgery as a part of enhanced recovery after surgery pathway in treatment of spontaneous pneumothorax. Data of 150 patients who underwent surgical treatment were  retrospectively analyzed. Among them group 1 of 75 patients underwent video-assisted thoracoscopic surgery (VATS) and group 2 of 75 patients underwent non-intubated VATS surgical treatment. All patients underwent atypical resection of the lung and pleural abrasion, diaphragm augmentation with mesh if diaphragm endometriosis was suspected. The perioperative data, short-term outcomes and recurrence rates of these two groups were compared. The two groups had comparable demographic, perioperative investigations, fluid infusions during surgery, the volume of surgery intraoperatively, blood loss, time for chest drain removal, length of stay in the hospital and the rate of complications. There were no conversions to thoracotomy or intubated general anaesthesia, no mortality. The peak end-tidal carbon dioxide was significantly higher in the non-intubated group than in the intubated group (mean: 48±8.6 vs 34±6.2 mmHg, p<0.001). The mean follow-up was 20.2±3.9 months in the non-intubated group and 24.7±4.2 months in the intubated group (p>0.05). Chest tube duration was 4.11 days in group 1 and 3.76 days in group 2. The recurrence rate of pneumothorax after surgery was 4% in both groups. Nnon-intubated video-assisted thoracic surgery for spontaneous pneumothorax could be considered a feasible, safe and effective method of treatment, even with mesh diaphragm augmentation, in cases of catamenial pneumothorax and can be a part of Enhanced Recovery After Surgery pathway. Continious follow-up and additional  clinical investigations are supposed to validate the profits of the suggested approach.